The Effects of Patient Health Information Seeking in Online Health Communities on Patient Compliance in China: Social Perspective - Xinyi Lu (JMIR Publications, 2023)
BackgroundOnline health communities (OHCs) can alleviate the uneven distribution and use of medical resources and severe hospital congestion. Patients may seek health information through OHCs before or after visiting physicians, which may affect their cognition, health literacy, decision-making preferences, and health-related behaviors such as compliance. Social factors (social support, social presence, and responsiveness) are closely related to patients' health information-seeking behavior and are significantly considered in OHCs. ObjectiveThis study aimed to explore the effects of patients' health information-seeking behavior (way and effectiveness) on compliance with physicians from the perspectives of patients' perceived social support, social presence, and responsiveness. MethodsThis study established a research model from the perspective of social information processing by using the social exchange theory. An anonymous questionnaire survey was conducted with several Chinese OHCs to collect data. Partial least squares and structural equation modeling were adopted to test the hypotheses and develop the model. ResultsThis study received 403 responses, of which 332 were valid, giving a validity rate of 82.4% (332/403). Among the sample, 78.6% (261/332) of the individuals were aged between 20 and 40 years, 59.3% (197/332) were woman, 69.9% (232/332) lived in urban areas, and 50% (166/332) had at least a bachelor's degree. The reliability, convergent validity, and discriminant validity were acceptable. Both the way and effectiveness of patients seeking health information through OHCs have a positive impact on their compliance through the mediation of their perceived social support, social presence, and responsiveness from OHCs and other users, and patient compliance can be improved by guiding patient health information-seeking behavior in OHCs from a social perspective. ConclusionsThis study proposes a research model to corroborate that patient health information-seeking behavior (way and effectiveness) in OHCs exerts positive effects on patient compliance with the treatment and physician's advice and provides suggestions for patients, physicians, and OHC service providers in China to help guide patients' health-related behaviors through OHCs to improve patient compliance, patient satisfaction, treatment efficiency, and health outcomes.